Erratum to “Vine tea (Ampelopsis grossedentata): A review of chemical composition, functional properties, and potential food applications” [J. Funct. Foods 76 (2021) 104317] - Carneiro, Renata C.V.; Ye, Liyun; Baek, Naerin; Teixeira, Gustavo H.A. [UNESP]; O'Keefe, Sean F. (Elsevier, 2021)
The publisher regrets that the conflict-of-interest statement was missed during the publication process. The publisher would like to apologise for any inconvenience caused.
Erratum to “Vine tea (Ampelopsis grossedentata): A review of chemical composition, functional properties, and potential food applications” [J.Funct. Foods 76 (2021) 104317](S1756464620305417)(10.1016/j.jff.2020.104317)